Methods for studying pulmonary lymphatics. Issue 5 (20th May 2021) - Maldonado-Zimbron, Victor E.; Hong, Jiwon; Russell, Peter; Trevaskis, Natalie L.; Windsor, John Albert; Phillips, Anthony Ronald John
The pulmonary lymphatics are critical for proper lung function, yet seldom considered in lung pathology. Newer and more convenient methods for studying lung lymphatics are now available and might create new diagnosis and treatment opportunities. https://bit.ly/3ldJGeo